The Role Of Context In Arabic Linguistics: The Story Of Abraham's Performance in Quran - Attia Abdulhameed Abdulqader (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This article investigates linguistic variance in narrating the same stories in different locations in the Quran. The research deals with repeating some scenes in the Qur’anic stories in multiple places in the Holy Qur’an, with the difference in the linguistic expression methods of the exact scene in its different locations, as well as the impact of the Qur’anic context on this difference. The study discusses the story of Abraham as a model for practice. The first topic was devoted to the theoretical study that sheds light on some crucial issues related to research. The second topic was devoted to the applied study in two parts. The conclusion presented the most important findings of the investigation, including that the Qur’anic stories do not have repetition in their literal sense. However, the Qur’an gives each place a part of the story according to what the context requires. The scene occurs in more than one location of the Qur’an. Yet, it is narrated in every place in a different linguistic performance in harmony with the Qur’anic context, represented in the present article’s evidence surrounding the Qur’anic story. Study findings help draw the attention of Arabic language learners to an interesting linguistic phenomenon in the Qur’anic levels and the function it serves in the story.